Fiscal decentralization, energy security, economic growth, and tourism nexus: Evidence from big six economies - Ul-Haq, Jabbar; Mushtaq, Shahzad; Visas, Hubert; Hye, Qazi Muhammad Adnan; Rehan, Raja (Journal of Tourism Management Research, 2023)
The travel and tourism industry contributes significantly to economic growth, global connectivity, and quality of life. We investigate the relationship between fiscal decentralization, energy security, economic growth, and tourism for the leading-six economies (namely China, France, Germany, Japan, the UK, and the USA) from 1995 to 2018 and examine the existence of the Kuznets curve (KC) between TR and FDC. Feasible generalized least squares (FGLS) and Panel corrected standard errors (PCSE) are employed for empirical examination of the liaison between the said variables. In the leading six economies, we find evidence for the N-shaped Kuznets curve. Fiscal decentralization (FDC), economic growth (EG), and energy security (ES) promote tourism. Other controls, such as tourism development and urbanization, are also included in the core model to check the robustness of the results. Our findings are insensitive to the integration of the other controls and econometric models. We find a positive relationship between urbanization, tourism development, and tourism, emphasizing the importance of tourism development and urbanization. The policy implication is that the top six economies can achieve sustainable growth in tourism by decentralizing their fiscal policies, boosting their economic growth, and ensuring their energy securities.